Virtual academic conferences as learning spaces: Factors associated with the perceived value of purely virtual conferences. (3rd November 2021) - Seidenberg, Nina; Scheffel, Maren; Kovanovic, Vitomir; Lynch, Grace; Drachsler, Hendrik
Abstract: Background: The COVID‐19 outbreak came with an unprecedented opportunity to investigate how the new reality of social distancing and limited international travel will affect the organization of academic conferences. Objectives: Drawing on conceptualization of academic conferences as professional learning spaces, in this study, we examine the factors associated with the perceived value of purely virtual academic conferences and how such perceptions differ between participants from different research fields. The aim was to gain knowledge about factors that should be considered when designing a virtual conference. Methods: Survey data from participants of three different virtual conferences were collected ( N  = 311). Kendall's rank correlation and χ 2 ‐analyses were performed. Results and Conclusion: Results show satisfaction with social interaction, the extent to which presentations met participants' topics of interest and the perceived importance of learning and getting an overview on the research topic to be related to the value rating. Researchers from different research fields differ significantly in their opinion about the most appropriate conference format regarding getting an overview on the research topic. For some researchers, virtual participation might be a valuable alternative to attending a conference in person. The study serves as a first attempt to understand how and for which target groups virtual conferences serve as a valuable learning event. Further research on this conference format is needed. Lay Description: What is already known about the topic: Prior to the pandemic only a few academic conferences were held purely virtual, thus scientific knowledge about this event format was rather scarce. Research on face‐to‐face conferences identified these events as platforms for networking and learning with a focus on social interaction. Mainly informal social interaction and networking is limited in the virtual space. What this paper adds: First insights how and for which target groups virtual conferences serve as a valuable learning event. Perceptions about the most appropriate conference format regarding certain conference aspects among researchers from different fields. Implications for practice: Formal interaction opportunities should be considered when designing a virtual conference. Virtual conferences are valuable events especially for those people, who focus on learning.